Analisis Geometrik Jalan sebagai Upaya Peningkatan Kinerja di Ruas Jalan Lingkar Selatan Kota Serang - Muhammad Fairuz Kamil; Adita Utami (Jurnal Teknik Sipil, 2026)
This study focuses on the geometric widening design of the South Ring Road (Jalan Lingkar Selatan) in Serang City, which is classified as a primary collector road. The main objective of this research is to optimize road performance while enhancing traffic safety by referring to the applicable geometric road design standards in Indonesia. The analysis is based on field survey data, including traffic volume, lane width, shoulder width, curve characteristics, and stopping sight distance. The existing road condition shows a total width of 6.5 meters, consisting of two lanes with a width of 3.25 meters each, and shoulders of 1 meter on each side. Based on the geometric evaluation, a road widening is proposed to increase the total width to 9 meters, with each lane expanded to 4.5 meters, while the shoulder width is maintained. The design refers to RSNI T-14-2004 as the guiding standard. This geometric improvement is expected to increase road capacity, reduce accident risk, and support the development of transportation infrastructure in the southern area of Serang City.